Digital pedagogy perspectives: exploring ESL teachers’ beliefs towards online-based ESL writing instruction - Fay Fiona Constantine Limbai; Asmaa AlSaqqaf (Human Resource Management Academic Research Society, 2024)
The COVID-19 pandemic necessitated the closure of schools worldwide to safeguard public health, resulting in unprecedented disruptions to education. These changes profoundly affected teachers, significantly altering their roles and responsibilities. This study aims to investigate the impact of school closures on the perspectives of ESL teachers in Sabah, Malaysia, regarding online-based instruction of ESL writing skills. A quantitative approach was employed, utilizing a descriptive and survey-based methodology to examine teachers’ beliefs and attitudes towards online ESL writing instruction. The study gathered data on various demographic factors, including the type of school (public or private), participants’ gender, age, and professional experience. The results reveal no significant differences in the attitudes and beliefs of public and private school ESL teachers in Sabah concerning the effects of online based education. Notably, the forced transition to online education during the pandemic may have catalysed future innovations, paving the way for a more effective hybrid education model.